1989
DOI: 10.1007/bf00210668
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of ?-thalassemia in Thailand: analysis of ?-thalassemia mutations using the polymerase chain reaction

Abstract: beta-Thalassemia mutations in 71 chromosomes of Thai patients from the northeast, the middle and the south of the country were investigated using dot blot hybridization of PCR (polymerase chain reaction)-amplified DNA with allele-specific oligonucleotide probes. Eight different known molecular defects were detected, at different frequencies. There was an amber mutation in codon 17, a C-T transversion at position 654 of IVS-2, a frameshift mutation between codons 71 and 72, an A-G transition at nucleotide -28 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
1

Year Published

1993
1993
2006
2006

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 15 publications
5
48
1
Order By: Relevance
“…Geographically, the region is situated in the middle part of the Malayu peninsula, between the mainland of Thailand and Malaysia. Previous study has suggested that the population in this region was an admixture of two ethnic factions, the Chinese-Thai extract from the Thai mainland and the Malay-Thai extract, which is predominantly Muslim (Fucharoen et al 1989;Laosombat et al 1992). …”
Section: Discussionmentioning
confidence: 95%
“…Geographically, the region is situated in the middle part of the Malayu peninsula, between the mainland of Thailand and Malaysia. Previous study has suggested that the population in this region was an admixture of two ethnic factions, the Chinese-Thai extract from the Thai mainland and the Malay-Thai extract, which is predominantly Muslim (Fucharoen et al 1989;Laosombat et al 1992). …”
Section: Discussionmentioning
confidence: 95%
“…Hb analysis using an automated cation exchange HPLC (VARIANT, Bio-Rad Laboratories, Hercules, CA) demonstrated Hb A 2 A pattern with the amount of Hb A 2 at 5.6%, characteristic of a b-thalassemia carrier. Further DNA analysis of the b-globin gene by the polymerase chain reaction (PCR) routinely run in our laboratory revealed that the proband carried a -28 A-G/b + -thalassemia mutation which is one of the common b-thalassemia genes in Thailand [7]. DNA analysis of a-globin gene cluster identified no a-thalassemia mutations, namely, a…”
Section: Case Reportmentioning
confidence: 90%
“…Amplification of the AAT gene of the proband and direct sequencing of the PCR-amplified products were performed under the condition as described (Fucharoen et al, 1989;Matsunaga et al, 1990). The sequence of primers used for amplification of the coding exons of the AAT gene was as follows :…”
Section: Patientmentioning
confidence: 99%
“…Amplified products of exon II were dot-blotted onto nylon membrane and hybridized with allele-specific oligonucleotide probes at 42~ for 1 hr and then washed at 55~ for l0 rain (Fucharoen et al, 1989). The sequence of the two probes was as follows:…”
Section: Patientmentioning
confidence: 99%